The Relationship Between Stroke Subtypes and Cognitive Function in Ischemic Stroke Patients at Siloam Hospital Lippo Village - Maurensia; Vivien Puspitasari (Universitas Pelita Harapan, 2025)
Introduction: Stroke is the second leading cause of death and a major cause of disability worldwide, including in Indonesia, and has an impact on cognitive function. Stroke can be classified based on the Bamford system into: Lacunar Infarct (LACI), Partial Anterior Circulation Infarct (PACI), Posterior Circulation Infarct (POCI), and Total Anterior Circulation Infarct (TACI), each with distinct clinical characteristics and lesion locations. This study aims to analyze the relationship between stroke subtypes and cognitive function in ischemic stroke patients using the MoCA- Ina questionnaire, to understand the clinical symptom differences and predict anatomical lesion sites in ischemic stroke subtypes based on the Bamford classification. Methods: This was a cross-sectional analytical study involving 40 ischemic stroke patients. Data were collected using the MoCA-Ina questionnaire to assess the cognitive function of ischemic stroke patients. Results: There was a significant relationship between stroke subtypes (anterior vs. posterior circulation) and cognitive function in ischemic stroke patients (P-value = 0.000), where patients with anterior circulation involvement showed greater cognitive impairment than those with posterior involvement. Conclusions: There is an association between stroke subtype and cognitive function in ischemic stroke patients at Siloam Hospital Lippo Village, particularly affecting the cognitive domains of language, delayed recall, abstraction, and attention.